Rectal adenocarcinoma: rare metastasis to the optic nerve. Issue 1 (24th January 2019) - Jamall, Omer; Theodoraki, Korina; Amin, Sepideh; Verity, David; Bates, Adam
Abstract : We present the first reported case of histologically proven colorectal adenocarcinoma with metastatic spread to the optic nerve. A 49-year-old man, with a known history of rectal adenocarcinoma, presented with progressive loss of vision in his left eye. On presentation, he had no perception to light in his left eye and Snellen acuity of 6/36 in the right eye. Fundus examination showed a left globally swollen optic nerve with a few flame-shaped haemorrhages. A gadolinium-enhanced MRI scan demonstrated abnormal thickening of the anterior and mid-section of the optic nerve with high signal on STIR and postgadolinium enhancement. Optic nerve biopsy confirmed the presence of epithelial adenocarcinoma compatible with metastasis of gut origin. The patient died within 4 months of presentation.